2016
DOI: 10.4172/2153-0602.1000195
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Immune Phenotype of Endothelial Cell-derived Micro Particles: The Missing Link between Diabetes-related States and Risk of Cardiovascular Complications?

Abstract: Type two diabetes mellitus (T2DM) remains a leading contributor to cardiovascular (CV) mortality worldwide. Although obese and metabolic syndrome are discussed key factors contributing a higher risk of T2DM, the exact molecular mechanisms underlying to the progression of dysmetabolic states are still not completely clear. There is large body of evidence regarding endothelial dysfunction as a key player in increasing CV risk and that vascular damage in the dysmetabolic patients might mediate through an imbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…There is strong association between immune patterns of MPs originated from different cells (endothelial cells, mononuclears, dendritic cells, and platelets) and nature evolution of various diseases including cardiovascular (CV) diseases, diabetes mellitus, abdominal obesity, cancer, sepsis, eclampsia, autoimmune states, infections and thrombosis [5][6][7][8][9][10]. Moreover, number of circulating MPs has been hypothesized to be responsible for prediction of the CV risk, thromboembolic events, autoimmune crisis, bleeding, as well as risk of all-cause mortality and CV death [11][12][13][14]. In this context, measure of MPs in circulation is considered a pretty promising, not simple tool for improving personal risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong association between immune patterns of MPs originated from different cells (endothelial cells, mononuclears, dendritic cells, and platelets) and nature evolution of various diseases including cardiovascular (CV) diseases, diabetes mellitus, abdominal obesity, cancer, sepsis, eclampsia, autoimmune states, infections and thrombosis [5][6][7][8][9][10]. Moreover, number of circulating MPs has been hypothesized to be responsible for prediction of the CV risk, thromboembolic events, autoimmune crisis, bleeding, as well as risk of all-cause mortality and CV death [11][12][13][14]. In this context, measure of MPs in circulation is considered a pretty promising, not simple tool for improving personal risk stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is a large body of strong evidence regarding influence of cardiovascular (CV) risk factors and or metabolic comorbidities on depletion of EPCs' number and appearance of their dysfunction [5][6][7][8]. Additionally, whether weak function and lowered number of EPCs appear in a peripheral blood prior to hypertension in pregnancy is not clear [9].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of EPCs for self-renewal and differentiation into mature endothelial cells has recently been under intense investigation [28] and remains of high interest for regenerative medicine [29]. Recent pre-clinical and clinical studies have shown a key role of bone marrow EPCs in the endothelial repair, angiogenesis, neovascularization, and attenuation of vascular function, whereas EPCs derived from peripheral blood cells including circulating mononuclears are under tight epigenetic control, and several paracrine and metabolic mechanisms and they are considered a central mechanism of immediate reparative response of injury [30]. There is evidence regarding that the both subpopulations of EPCs are mobilized or released into systemic circulation in response to specific stimuli.…”
Section: Introductionmentioning
confidence: 99%